PERAN TEKNOLOGI DALAM PEMBELAJARAN PEMROGRAMAN DI KELAS XI SMKS TELKOM - Eky Pratama Putra, Ryan; Ardy Prihantana, Hendrawan; Abadi, Machrus (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2024)
The development of technology has become a very important thing in the course of life. Nowadays, we have entered the era of the industrial revolution 4.0, which is a technological development marked by the massive advancement of the internet. The rapid development of technology has given birth to various innovations in learning, one of which is the integration of technology in the teaching and learning process. SMKS Telkom Sandhy Putra as one of the vocational schools that focuses on the field of information technology. This study aims to determine the role of technology in improving the programming learning experience at SMKS Telkom Shandy Putra. Through a qualitative and descriptive approach, this study explores the effectiveness and motivation of student learning with the use of technology in learning. The data obtained from this study are primary data in the form of in-depth interviews with students and teachers, as well as direct observation of the learning process. Then, the technique used in the study is to use qualitative data analysis techniques. According to the results of the study, it can be concluded that the use of technology in programming learning at SMKS Telkom Sandhy Putra has proven effective in improving students' understanding of the basic concepts of programming.